Stable isotope and multi-analytical investigation of Monte da Cegonha: A Late Antiquity population in southern Portugal - Saragoça, Patrícia (2017)
This study presents for the first time the diet of a Late Antiquity population in southern Portugal (Civitas of Pax Julia), from the Roman villa of Monte da Cegonha (predominantly 7th century CE). Stable isotope analysis (δ13C, δ15N, δ18O, 87Sr/86Sr) of human and faunal bone collagen and apatite was conducted in order to understand the influence of Roman subsistence strategies on the way of life of rural inhabitants of the area of Pax Julia and to explore their diet (types of ingested plants, amount of animal resources, terrestrial versus marine resources). X-ray diffraction (XRD) and Fourier transform infra-red spectroscopy (FTIR) analyses were used to determine the degree of bone diagenesis and assess the reliability of the bone stable isotopic composition for palaeodietary reconstruction. Anthropological analysis revealed a cariogenic diet, rich in starchy food and carbohydrates, in at least in two individuals based on the frequency of dental caries. Collagen and apatite carbon isotopic analysis suggested that C3 plants were the basis of the population's diet, complemented with some terrestrial meat and its by-products as reflected by the observed bone collagen nitrogen isotopic composition. Moreover, whilst the fairly low apatite-collagen spacing recorded in some skeletons (at around 4‰) may have been due to freshwater organisms intake, the relatively low nitrogen values observed indicate that this consumption did not occur very often, unless in the form of fresh fish of low trophic level or fish sauces. There were no significant differences in isotopic values depending on gender or burial type. Strontium and oxygen isotopic composition of bone apatite revealed a sedentary community, with the exception of a male individual who probably did not spend his childhood in Monte da Cegonha.